Inklusivitas Pengelolaan Alokasi Dana Desa (ADD) Berbasis Partisipasi Masyarakat di Desa Air Mata, Kabupaten Kupang - Pariangu, Umbu TW (JAP UNWIRA, 2020)
Community participation in the management of village allocation fund in the Village of Mata Air is still far from the requiredstandards. At the planning stage, the management of the fund is deemed as too “technocratic” in which only village elites areinvolved, while the poor segment of the village residents as well as women are not involved. At the implementation stage, thefund management has neither been institutionalized nor determined by the mobilization of government instruments andvillage administrative personnel. So far the community participation only goes in a spontaneous way and as such has reducedthe degree of inclusiveness. As a result, the continuity of villagers’ initiatives is cut off and therefore it does not nurture thesense of belonging in the whole village development. At the supervision level, the fund is controlled in a structural-hierarchicalway without involving the village residents. The residents are not given access to the village fund management. The villagehead, village finance technical executive, and the village treasurer are still considered the most responsible persons in themanagement of village allocation fund.